Cortical gyrification in children with attention deficit-hyperactivity disorder and prenatal alcohol exposure. (1st August 2021) - Kilpatrick, Lisa A.; Joshi, Shantanu H.; O'Neill, Joseph; Kalender, Guldamla; Dillon, Andrea; Best, Karin M.; Narr, Katherine L.; Alger, Jeffry R.; Levitt, Jennifer G.; O'Connor, Mary J.
Highlights: ADHD+PAE may be a distinct ADHD subtype, with neurodevelopmental differences. Children with ADHD+PAE uniquely demonstrate lower mid-dorsolateral gyrification. Widespread lower gyrification relates to more severe facial dysmorphia, impairments. Abstract: Background: An improved understanding of the neurodevelopmental differences between attention deficit hyperactivity disorder with and without prenatal alcohol exposure (ADHD + PAE and ADHD-PAE, respectively) is needed. Herein, we evaluated gyrification (cortical folding) in children with ADHD + PAE compared to that in children with familial ADHD-PAE and typically developing (TD) children. Methods: ADHD + PAE (n = 37), ADHD-PAE (n = 25), and TD children (n = 27), aged 8–13 years, were compared on facial morphological, neurobehavioral, and neuroimaging assessments. Local gyrification index (LGI) maps were compared between groups using general linear modelling. Relationships between LGI and clincobehavioral parameters in children with ADHD ± PAE were evaluated using multivariate partial least squares. Results: ADHD + PAE and ADHD-PAE groups showed significantly lower LGI (relative to TD) in numerous regions, overlapping in medial prefrontal, parietal, and temporo-occipital cortices (p < 0.001). However, LGI in left mid-dorsolateral prefrontal cortex was uniquely lower in the ADHD + PAE group (p < 0.001). Partial least squares analysis identified one significant latent variable (accounting for 59.3 % of the crossblock correlation, p < 0.001), reflecting a significant relationship between a profile of lower LGI in prefrontal (including left mid-dorsolateral), insular, cingulate, temporal, and parietal cortices and a clinicobehavioral profile of PAE, including a flat philtrum and upper vermillion border, lower IQ, poorer behavioral regulation scores, and greater hyperactivity/impulsivity. Conclusions: Children with ADHD + PAE uniquely demonstrate lower mid-dorsolateral LGI, with widespread lower LGI related to more severe facial dysmorphia and neurobehavioral impairments. These findings add insight into the brain bases of PAE symptoms, potentially informing more targeted ADHD treatments based on an objective differential diagnosis of ADHD + PAE vs. ADHD-PAE.